Human alveolar macrophage metabolism is compromised during Mycobacterium tuberculosis infection - Mendonca, Laura E.; Pernet, Erwan; Khan, Nargis; Sanz, Joaquin; Kaufmann, Eva; Downey, Jeffrey; Grant, Alexandre; Orlova, Marianna; Schurr, Erwin; Krawczyk, Connie; Jones, Russell G.; Barreiro, Luis B.; et al. (Frontiers in Immunology, 2023)
Pulmonary macrophages have two distinct ontogenies: long-lived embryonically-seeded alveolar macrophages (AM) and bone marrow-derived macrophages (BMDM). Here, we show that after infection with a virulent strain of Mycobacterium tuberculosis (H37Rv), primary murine AM exhibit a unique transcriptomic signature characterized by metabolic reprogramming distinct from conventional BMDM. In contrast to BMDM, AM failed to shift from oxidative phosphorylation (OXPHOS) to glycolysis and consequently were unable to control infection with an avirulent strain (H37Ra). Importantly, healthy human AM infected with H37Ra equally demonstrated diminished energetics, recapitulating our observation in the murine model system. However, the results from seahorse showed that the shift towards glycolysis in both AM and BMDM was inhibited by H37Rv. We further demonstrated that pharmacological (e.g. metformin or the iron chelator desferrioxamine) reprogramming of AM towards glycolysis reduced necrosis and enhanced AM capacity to control H37Rv growth. Together, our results indicate that the unique bioenergetics of AM renders these cells a perfect target for Mtb survival and that metabolic reprogramming may be a viable host adjunctive therapy against TB.